CRISPR/Cas9-mediated knockout of a polyester synthase-like gene delays flowering time in alfalfa - Galindo Sotomonte, Luisa Fernanda; Jozefkowicz, Cintia; Gomez, Maria Cristina; Stritzler, Margarita; Frare, Romina Alejandra; Bottero, Ana Emilia; Tajima, Hiromi; Blumwald, Eduardo; Ayub, Nicolás Daniel; Soto, Gabriela Cynthia (Springer, 2023)
Alfalfa (Medicago sativa), commonly known as the “Queen of Forages”, is the main source of plant protein for meat and milk production systems worldwide. Since alfalfa is a perennial vegetative-harvest forage, delaying flowering is a promising strategy to increase alfalfa biomass yield and quality (Adhikari et al. 2019). The production of transgenic alfalfa either overexpressing or underexpressing different genes has led to delayed flowering phenotypes (Lorenzo et al. 2020; Ma et al. 2021). Unfortunately, the deregulation of transgenic events involves long-term and expensive procedures that limit their commercial utilization. The recently described increased efficiency of the CRISPR/Cas9 system in regenerative alfalfa allowed full allelic knockout of target genes, and the production of edited alfalfa plants (Stritzler et al. 2022), opening the way for a new generation of transgene-free alfalfa varieties displaying delayed flowering.